Initial performance of the GlueX DIRC detector. Issue 1 (1st November 2022) - Ali, A; Barbosa, F; Bessuille, J; Chudakov, E; Dzhygadlo, R; Fanelli, C; Frye, J; Hardin, J; Hurley, A; Ihloff, E; Kalicy, G; Kelsey, J; et al.
Abstract : The GlueX experiment at Jefferson Laboratory aims to perform quantitative tests of non-perturbative QCD by studying the spectrum of light-quark mesons and baryons. A Detector of Internally Reflected Cherenkov light (DIRC) was installed to enhance the particle identification (PID) capability of the GlueX experiment by providing clean π /K separation up to 3.7 GeV/ c momentum in the forward region ( θ < 11°), which will allow the study of hybrid mesons decaying into kaon final states with significantly higher efficiency and purity. The new PID system is constructed with radiators from the decommissioned BaBar DIRC counter, combined with new compact photon cameras based on the SuperB FDIRC concept. The full system was successfully installed and commissioned with beam during 2019/2020. The initial PID performance of the system was evaluated and compared to one from Geant4 simulation.